Heat pulse propagation and anomalous electron heat transport measurements on the optimized stellarator W7-X. (26th March 2021) - Weir, G.M.; Xanthopoulos, P.; Hirsch, M.; Höfel, U.; Stange, T.; Pablant, N.; Grulke, O.; Äkäslompolo, S.; Alcusón, J.; Bozhenkov, S.; Beurskens, M.; Dinklage, A.; et al.
Abstract: The optimized stellarator Wendelstein 7-X (W7-X) is designed to have an approximately quasi-isodynamic magnetic configuration with reduced neoclassical transport in comparison to a classical stellarator, and turbulent transport is expected to be a significant source of anomalous heat transport across the plasma minor radius. The ion temperature gradient driven mode and the trapped electron mode (TEM) are thought to be responsible for the ion-scale turbulence in W7-X plasmas with volume averaged pressure below 1%. In this work, the electron temperature gradient driven turbulence is shown to be a good candidate for the explanation of the observed electron heat flux, in the inner plasma region where the density gradient is weak (in the outer region, a relatively stronger density gradient would drive additional TEM turbulence). The experimental electron heat transport measured during electron cyclotron resonant heating power and plasma density scans is compared to neoclassical predictions, and the stiffness in the electron heat transport measured during transient transport experiments is presented in three common magnetic configurations of W7-X. In low-⟨ β ⟩ plasma discharges, the stiffness in the electron heat flux, quantified by the ratio of the heat pulse to power balance diffusivity, χ e H P / χ e P B, is measured to be less than 2, and trend downwards with increasing collisionality.